Synthesis of a Series of Novel 3,9-Disubstituted Phenanthrenes as Analogues of Known N-Methyl-d-aspartate Receptor Allosteric Modulators - Irvine, Mark W.; Fang, Guangyu; Eaves, Richard; Mayo-Martin, Maria B.; Burnell, Erica S.; Costa, Blaise M.; Culley, Georgia R.; Volianskis, Arturas; Collingridge, Graham L.; Monaghan, Daniel T.; Jane, David E. (Synthesis, 2015)
9-Substituted phenanthrene-3-carboxylic acids have been reported to have allosteric modulatory activity at the N-methyl-d-aspartate (NMDA) receptor. This receptor is activated by the excitatory neurotransmitter l-glutamate and has been implicated in a range of neurological disorders such as schizophrenia, epilepsy and chronic pain, and in neurodegenerative disorders such as Alzheimer’s disease. Herein, the convenient synthesis of a wide range of novel 3,9-disubstituted phenanthrene derivatives starting from a few common intermediates is described. These new phenanthrene derivatives will help to clarify the structural requirements for allosteric modulation of the NMDA receptor.
Keywords: phenanthrenes; NMDA receptor; allosteric modulators; palladium coupling; Wittig reaction